(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
During a trial carried out in 1989 and 1990 on tomato plants in a greenhouse placed in Sarzana (La Spezia, Italy), an interesting Mirid, Dicyphus errans (Wolft) (Heteroptera Miridae) was found aboundant on the crop. It was observed mainly as predator of all the preimaginal stages of Myzus persicae and also of adults and eggs of Trialeurodes vaporariorum, even if it had also a phytophagous diet, especially during the periods in which the preys were rare. The Dicyphus appeared on the tomato plants in April-May and all the preimaginal stages of it were observed on other crops and spontaneous plants until November. Even if its activity as predator has still to be quantified, the Dicyphus errans appears as a potential natural enemy of aphids and white-flies which could be employed in integrated and/or biological control programs in the greenhouses.